Comorbidity, not patient age, is associated with impaired safety outcomes in vedolizumab‐ and ustekinumab‐treated patients with inflammatory bowel disease—a prospective multicentre cohort study. Issue 8 (9th September 2020) - Asscher, Vera E. R.; Biemans, Vince B. C.; Pierik, Marieke J.; Dijkstra, Gerard; Löwenberg, Mark; van der Marel, Sander; de Boer, Nanne K. H.; Bodelier, Alexander G. L.; Jansen, Jeroen M.; West, Rachel L.; Haans, Jeoffrey J. L.; van Dop, Willemijn A.; et al.
Summary: Background: Few data are available on the effects of age and comorbidity on treatment outcomes of vedolizumab and ustekinumab in inflammatory bowel disease (IBD). Aims: To evaluate the association between age and comorbidity with safety and effectiveness outcomes of vedolizumab and ustekinumab in IBD. Methods: IBD patients initiating vedolizumab or ustekinumab in regular care were enrolled prospectively. Comorbidity prevalence was assessed using the Charlson Comorbidity Index (CCI). Association between age and CCI, both continuously assessed, with safety outcomes (any infection, hospitalisation, adverse events) during treatment, and effectiveness outcomes (clinical response and remission, corticosteroid‐free remission, clinical remission combined with biochemical remission) after 52 weeks of treatment were evaluated. Multivariable logistic regression was used to adjust for confounders. Results: We included 203 vedolizumab‐ and 207 ustekinumab‐treated IBD patients, mean age 42.2 (SD 16.0) and 41.6 (SD 14.4). Median treatment duration 54.0 (IQR 19.9‐104.0) and 48.4 (IQR 24.4‐55.1) weeks, median follow‐up time 104.0 (IQR 103.1‐104.0) and 52.0 weeks (IQR 49.3‐100.4). On vedolizumab, CCI associated independently with any infection (OR 1.387, 95% CI 1.022‐1.883, P = 0.036) and hospitalisation (OR 1.586, 95% CI 1.127‐2.231, P = 0.008). On ustekinumab, CCI associated independently with hospitalisation (OR 1.621, 95% CI 1.034‐2.541, P = 0.035). CCI was not associated with effectiveness, and age was not associated with any outcomes. Conclusions: Comorbidity ‐ but not age ‐ is associated with an increased risk of hospitalisations on either treatment, and with any infection on vedolizumab. This underlines the importance of comorbidity assessment and safety monitoring of IBD patients.